2015
DOI: 10.1007/s12020-015-0655-1
|View full text |Cite
|
Sign up to set email alerts
|

Is prolactin the missing link in adipose tissue dysfunction of polycystic ovary syndrome patients?

Abstract: The aims of the study were to evaluate whether adiposity was among the determinants of circulating prolactin levels and to determine whether serum prolactin independently predicted metabolic abnormalities in patients with polycystic ovary syndrome (PCOS). A total of 322 PCOS patients with normal serum prolactin levels were recruited between January 2007 and January 2014. Anthropometric, metabolic, and hormonal parameters were measured in all of the patients. HOMA-IR was calculated as an index of insulin resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 48 publications
2
25
0
2
Order By: Relevance
“…In a study, high physiological concentrations of PRL increased adiponectin release, showing a protective effect against metabolic dysfunction [28]. In another study, Albu et al [5] found a positive correlation between adiponectin and PRL levels in patients with PCOS. In this study, VAI, but not adiponectin, was found to be a useful marker for predicting serum PRL levels.…”
Section: Polycystic Ovary Syndrome Is a Reproductive Endocrinopathy mentioning
confidence: 92%
See 1 more Smart Citation
“…In a study, high physiological concentrations of PRL increased adiponectin release, showing a protective effect against metabolic dysfunction [28]. In another study, Albu et al [5] found a positive correlation between adiponectin and PRL levels in patients with PCOS. In this study, VAI, but not adiponectin, was found to be a useful marker for predicting serum PRL levels.…”
Section: Polycystic Ovary Syndrome Is a Reproductive Endocrinopathy mentioning
confidence: 92%
“…Although the regulation of PRL release is altered in PCOS patients, the relationship between PRL and adiposity is still unclear [5]. Therefore, the relationship between PRL and increased adipose tissue and metabolic disorders still remains to be elucidated in this patient population.…”
Section: E-issn: 2149-3189mentioning
confidence: 99%
“…Full texts of the remaining studies were obtained for eligibility assessment. As a result, 14 studies were included in this review [11,[15][16][17][18][19][20][21][22][23][24][25][26][27] .…”
Section: Data Extraction and Quality Assessmentmentioning
confidence: 99%
“…Nine studies were included with results on associations between serum PRL levels and BMI, WC, blood pressure, blood lipids, blood glucose, and insulin resistance [15,[18][19][20][21][22][23][24]27] . Among these studies, there were 3 prospective studies, 2 case-control studies, and 3…”
Section: Association Between Serum Prl Levels and Metabolic Markersmentioning
confidence: 99%
See 1 more Smart Citation